COMPARATIVE ASSESSMENT OF CENTRAL HEMODYNAMIC MONITORING METHODS IN CHILDREN AFTER CARDIAC SURGICAL INTERVENTIONS (Herald of the National Children's Medical Center, 2025)
The postoperative condition of children following cardiac surgical interventions requires highly accurate monitoring of central hemodynamics to enable early detection of hypoperfusion and heart failure. The use of both invasive and non-invasive methods (echocardiography, biochemical monitoring) allows for a comprehensive assessment of circulatory status in the setting of intensive care.
Keywords: cardiac surgery; children; hemodynamics; CVP (central venous pressure); echocardiography; lactate; monitoring; inotropic support